Artificial Intelligence development, opportunities and challenges - Nguyễn Thi Thu, Nga; Hoàng Đức Thọ; Trần Mạnh Đông; Phạm Duy Nam (Journal of Military Science and Technology, 2024)
The article presents the development process, opportunities and challenges of artificial intelligence (AI), a field with many practical applications: Medicine, Management Economics, Education, Military, etc. The scope of artificial intelligence includes algorithms, heuristics, genetic algorithms, expert systems, artificial neural networks, fuzzy logic, etc. The article also analyzes the creation of intelligent machines that can think and make decisions independently and the arbitrary and dangerous use of this technology that can lead to disaster (as in the case of nuclear energy). However, concerns about the reduced importance of humans are unfounded because humans not only create intelligent machines but also create machines with their own consciousness and personality.